Streamlining and simplification of surgical stent fabrication for micro‐endodontic surgery. (14th October 2020) - George, Roy; Cameron, Andrew; Meer, Mohammed
Abstract: Surgical stents allow clinicians to undertake micro‐endodontic surgical procedures with an increased level of accuracy. When planned in combination with cone‐beam computed tomography (CBCT) radiographic imaging, surgical stents can help accurately determine the point of entry of the surgical drill, minimise the size of the osteotomy, ensure accurate resection of the root/s and avoid vital anatomical structures. Fabrication of surgical stents can, however, be a complex and long‐drawn‐out process, adding to the cost of the surgery. This case report presents a relatively easy method of fabricating a surgical guide and showcases the benefits of a planned surgical guide in managing a periapical pathology with close proximity to the mental nerve canal.